Improvement of Quranic Reading Skills and Islamic Insight among Children and Adolescents in Tarai Bangun Village: a Participatory Action Research Approach - Suhendri Suhendri; Sopian Sinaga; Ahmad Zaky (As-sunnah: Jurnal Pengabdian Masyarakat, 2023)
This paper discusses the implementation of the Thematic Community Service Learning (KKN-T) program in Tarai Bangun Village, Tambang Sub-district, Kampar Regency, with the background of selecting a theme focusing on the need for religious and Islamic education in the village. The chosen theme for the KKN-T program is "Improving Quranic Reading Skills and Islamic Understanding for Children and Adolescents in Tarai Bangun Village, Tambang Sub-district, Kampar Regency" because the village has an urgent need to enhance religious knowledge and Islamic life, especially among the younger generation. In implementing this program, the participants follow a well-structured method of planning and executing activities. The activities involve intensive Quranic teaching, dawn sermons (kultum subuh), sermons before tarawih prayers (kultum before tarawih), and the imparting of Islamic values to the local community. During the implementation, data is collected through observation, interviews, and Quranic reading skill assessments, allowing for the collection and analysis of scientific findings. The scientific findings indicate that the KKN-T activities have had a significant and positive impact on improving Quranic reading skills among the children of Tarai Bangun Village. The data shows a tangible increase in the understanding of religion and Islamic awareness among children and adolescents. Furthermore, the program has successfully nurtured a sense of care and affection for Islam among them. The conclusion drawn from this research is that KKN-T can serve as an effective model for promoting religious and Islamic education and enhancing Quranic reading skills for children and adolescents in similar villages.